FILSAFAT MUHAMMAD ABID AL-JABIRI DALAM TELAAH EPISTEMOLOGI BURHANI SINERGI NALAR ISLAM - Hakim, Maman Lukmanul; Al-Habibi, Muhammad Luthfi Jalaludin (Living Islam: Journal of Islamic Discourses, 2024)
This research aims to discuss the study of Muhammad Abid Al-Jabiri Philosophy in Epistemology (Burhani) Synergy of Islamic Reason. This research uses a qualitative approach and applies descriptive-analytical methods. Philosophy is Positioned as a formal object, the material object is Muhammad Abid Al-Jabiri and the context is Epistemology (Burhani) and Islamic Reason. The result and discussion in this research show that Muhammad Abid Al-Jabiri Philosophy through his throughts on Islamic Reason is embedded in Burhani’s epistemologi through his curiosity about the domination of science which is based on the use of reason as the main human ability to obtain knowledge using the method of deducation. Culture it self a cultural heritage, thought, religion, literature, art, philosophy, sufism and kalam that comes from the past. This research concludes that Muhammad Abid Al-Jabiri, Epistemology Burhani (Philosophy) is relevant to be used synergi Islamic Reason and understand of texts and implied and explicit meanings in reality cause and effect (asbabun nuzul) of Islamic reason traditions in the present so as to forget the traditions of the history. Keywords: Epistemology Burhani; Islamic Reason; Muhammad Abid Al-Jabiri; Phylosophy; Turath   Penelitian ini bertujuan untuk membahas Telaah Filsafat Muhammad Abid Al-Jabiri dalam Epistemologi (Burhani) Sinergi Nalar Islam, Penelitian ini menggunakan pendekatan kualitatif serta menerapkan metode deskriptif-analitis, Filsafat di posisikan sebagai objek formal, objek materialnya Muhammad Abid Al-Jabiri serta konteksnya Epistemologi (Burhani) dan Nalar Islam. Hasil dan pembahasan pada penelitian ini menunjukkan bahwa Filsafat Muhammad Abid Al-Jabiri melalui pemikirannya tentang Nalar Islam tertera pada Epistemologi Burhani melalui rasa ingin tahunya pada pendominasian ilmu pengetahuan yang didasari dengan penggunaan akal untuk kemampuan utama manusia memperoleh ilmu pengetahuan tersebut dengan metode deduksi. Kebudayaan sendiri merupakan suatu warisan budaya, pemikiran, agama, sastra, seni, filsafat, tasawwuf dan kalam yang hadir dari kita maupun orang lain, baik itu dekat dan jauh, menyertai kekinian kita yang datang dari masa lalu. Penelitian ini menyimpulkan bahwa Epistemologi Burhani (Filsafat) Muhammad Abid Al-Jabiri relevan digunakan untuk mensinergikan Nalar Islam serta pemahaman akan teks dan makna yang tersirat serta tersurat dalam mengejawantahkan sebab-akibat (asbabun nuzul) tradisi nalar Islam pada masa sekarang hingga tidak melupakan tradisi masa lalu. Kata kunci: Epistemologi Burhani; Filsafat; Muhammad Abid Al-Jabiri; Nalar Islam; Turath